The Current State of Production and Future Estimation of Dry Beans Production in Turkey - Mehmet Aydoğan; Kürşat Demiryürek; Nur İlkay Abacı (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to reveal of future estimation of the dry bean production area, production quantity, export quantity, import quantity and supply-demand balance in Turkey. The data used in the study were obtained from the Turkish Statistical Institute (TIS), FAO and the Ministry of Food Agriculture and Livestock records. The Double exponential smoothing method was used to estimate the future data. The data was used in the analysis includes dry bean production areas (ha), quantity of production, export, import and domestic use between 1994 and 2014. In the next five years (2015-2019), it was forecasted that there would be a decrease in the amount of the dry bean production areas, production quantity and export quantity whereas there would be an increase in the amount of the dry bean import quantity and domestic use. At the same time, it was expected that the amount of dry bean domestic supply would be higher than dry bean domestic demand. The reason for this surplus is high import quantity. In other words, it was foreseen that Turkey’s external dependence in dry bean will increase. In order to ensure continuity of production, it should be increase the income of dry bean producers, decrease the dry bean production cost and encourage the production. The policies to prevent domestic prices fall should be developed.